The Use Of Autoplay Studio 4 Learning Media To Improve Student Learning Outcomes In Productive Computer Graphics Subjects At SMK NEGERI 7 JEMBER - Nur Hesti Pratiwi; Syamsul Muarif; Fajarisman Fajarisman; Asri Widiatsih Widiatsih (Journal of Education Technology and Inovation, 2023)
Productive learning majoring in DKV (Visual Communication Design) Computer Graphics at SMKN 7 Jember which provides a learning experience by using and developing skills in learning activities and being scientific. Therefore, what is needed is that the results of student learning can also influence the presentation of material or context in classroom learning process activities supported by learning media.Autoplay Studio 4 to facilitate the process of learning activities. The subjects in this research at SMKN 7 Jember were 28 male students, 16 male students and 12 female students. The aim of this research is to find out the results of students learning in Productive subjects, especially computer graphics, by utilizing learning mediaautoplay studio 4. This research uses a classroom action research research model which consists of two cycles with several stages of planning, implementation, observation and reflection. The data collection techniques used are observation, tests and documentation. And the results of this research in cycle I were 46% of student learning outcomes, while in cycle II it was 82%, so the value was 36% so it concluded that learning mediaautoplay studio 4 can improve student learning outcomes